1985
DOI: 10.1139/z85-026
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of a Mediterranean tortoise (Testudo hermanni): a declining population

Abstract: In France, wild tortoises occur at low densities (< 3/ha) in the mixed forest and maquis of the Massif des Maures. In an evergreen oak forest with scattered, traditional cultivations, distinct subpopulations still exist at relatively high density (> 10/ha). The population structure is heavily skewed in favour of old adults and recruitment is low. The population is declining due to habitat loss, both from fire and through the decline in traditional horticultural practices, leading to a reduction in nest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 5 publications
3
29
0
Order By: Relevance
“…Our study shows that the home range of the steppe tortoise (18 ha, using the MCP method) is noticeably large when compared with that of other Testudinidae species; all of which have a home range of only a few hectares (Rose and Judd 1975;Bertram 1979;McRae et al 1981;Stubbs and Swingland 1984;Naulleau 1988;Calzolai and Chelazzi 1991;Diemer 1992;Smith 1995;Hailey and Coulson 1996;Huot-Daubremont 1996;Smith et al 1997).…”
Section: Discussionmentioning
confidence: 66%
“…Our study shows that the home range of the steppe tortoise (18 ha, using the MCP method) is noticeably large when compared with that of other Testudinidae species; all of which have a home range of only a few hectares (Rose and Judd 1975;Bertram 1979;McRae et al 1981;Stubbs and Swingland 1984;Naulleau 1988;Calzolai and Chelazzi 1991;Diemer 1992;Smith 1995;Hailey and Coulson 1996;Huot-Daubremont 1996;Smith et al 1997).…”
Section: Discussionmentioning
confidence: 66%
“…The preference of T. graeca for low cover values has also been indicated by other authors (Wright et al 1988, Willemsem 1991. The strong selection for non-irrigated croplands could also be due to its role in egglaying, as is the case in other Testudo populations (Stubbs and Swingland 1984;Swingland and Stubbs 1985). On the other hand, it has been shown that the ecotones between crops and natural vegetation areas are optimum places for thermoregulation in the black rat snake (Blouin-Demers and Weatherhead 2001a, b), because they contain basking places near shadier areas where animals can cool down.…”
Section: Selection At Landscape Scalementioning
confidence: 99%
“…Our results are comforted by those of (Mazzotti et al, 2002) who attributed the Larger home ranges of Testudo hermanni which occur in northern Italy (4.6 ha in males and 7.4 ha in females) to food scarcity in this area. Th e high selection for cultivated land could also be due to their role in laying eggs, as is the case for other populations of Testudo graeca (Stubbs, Swingland, 1984). Th e vegetation structure is also an important factor because it infl uences microhabitats by controlling the penetration of the sunlight, which aff ects the microclimate at the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Unauthenticated Download Date | 5/9/18 7:32 PM ment criteria of Stubbs (Stubbs, Swingland, 1984). Th e body mass of the tortoises was measured by a digital balance (precision ± 1 g).…”
Section: R E S E a R C H P R O T O C O Lmentioning
confidence: 99%